Оптимальное управление сложными системами в случае неточного измерения на основе моделей сетей Петри - Копп, В. Я.; Качур, С. А. (НТУ "ХПИ", 2013)
Solution of task of tuning of the measuring system including a few different classes of measuring devices is offered, for the supervision after an object in the conditions of large apriori vagueness. A flow diagram and model of the measuring system with the use of the Petri nets is developed. Application of net model allows to reduce temporal expenses on the receipt of information about an object and promote the fast-acting of algorithms of management.
Keywords: система измерительная; измерители; неопределенность априорная; схема структурная; модель сетевая; алгоритм управления